GitLab: Work where you want, when you want - Prithwiraj Choudhury; Kevin Crowston; Linus Dahlander; Marco S. Minervini; Sumita Raghuram (Journal of Organization Design, 2020)
GitLab is a software company that works "all remote" at the scale of more than 1000 employees located in more than 60 countries. GitLab has no physical office and its employees can work from anywhere they choose. Any step of the organizational life of a GitLab employee (e.g., hiring, onboarding and firing) is performed remotely, except for a yearly companywide gathering. GitLab strongly relies on asynchronous coordination, allowing employees to work anytime they want. After highlighting some of the main practices implemented by GitLab to effectively work all remotely and asynchronously, I asked renowned organizational scientists their thoughts on this interesting case and to question the generalizability of the all remote asynchronous model. Understanding whether and under what conditions this model can succeed can be of guidance for organizational designers that are now considering different remote models in response of the COVID-19 shock and its aftermath.
Keywords: 650; Organizational design; New forms of organizing; Remote work; All remote; Virtual organizations; COVID-19